Trustworthiness in Indonesia healthcare: fostering loyalty in B2B relationships - Aswindaru Rinenggo; Achmad Sudiro; Sunaryo; Ananda Sabil Hussein (Cogent Business & Management, 2024)
The expansion of healthcare infrastructure has led to a surge in demand for diagnostic equipment, presenting opportunities for healthcare equipment suppliers. However, the market faces challenges, including intense competition exacerbated by limited product differentiation and a surplus of suppliers. Amidst this competitive landscape, understanding the factors influencing business consumer preferences and loyalty becomes crucial for suppliers. Theoretical perspectives highlight trust as a foundational element in business-to-business (B2B) relationships, influencing loyalty. Perceived value, reflecting consumer assessments of product quality, pricing, and relational benefits, mediates this relationship. Nevertheless, research on trust and loyalty in B2B healthcare markets, particularly in Indonesia, remains limited. Furthermore, the role of switching costs in shaping loyalty, especially in the context of healthcare equipment, is underexplored. Employing Structural Equation Modeling-Partial Least Squares (SEM-PLS), this study investigates trust, perceived value, switching costs, and loyalty dynamics between private hospitals and equipment providers in Java, Indonesia. Findings reveal that trust significantly influences loyalty, with perceived value partially mediating the trust-loyalty relationship. Surprisingly, switching costs do not moderate the trust-loyalty relationship. This study's contributions include clarifying trust and loyalty dynamics in B2B healthcare markets in Indonesia and underscoring the importance of perceived value in driving loyalty. Despite limitations, such as geographic scope, this research informs strategic marketing and relationship management in the healthcare equipment sector.
Keywords: 650; Trust; loyalty; B2B; healthcare; switching cost; perceived value